Effect of co-trimoxazole on mortality in HIV-exposed but uninfected children in Botswana (the Mpepu Study): a double-blind, randomised, placebo-controlled trial. Issue 5 (May 2017) - Lockman, Shahin; Hughes, Michael; Powis, Kate; Ajibola, Gbolahan; Bennett, Kara; Moyo, Sikhulile; van Widenfelt, Erik; Leidner, Jean; McIntosh, Kenneth; Mazhani, Loeto; Makhema, Joseph; Essex, Max; et al.
Summary: Background: Co-trimoxazole prophylaxis reduces mortality among HIV-infected children, but efficacy in HIV-exposed but uninfected (HEU) children in a non-malarial, low-breastfeeding setting with a low risk of mother-to-child transmission of HIV is unclear. Methods: HEU children in Botswana were randomly assigned to receive co-trimoxazole (100 mg/20 mg once daily until age 6 months and 200 mg/40 mg once daily thereafter) or placebo from age 14–34 days to age 15 months. Mothers chose whether to breastfeed or formula feed their children. Breastfed children were randomly assigned to breastfeeding for 6 months (Botswana guidelines) or 12 months (WHO guidelines). The primary outcome, analysed by a modified intention-to-treat approach, was cumulative child mortality from treatment assignment to age 18 months. We also assessed HIV-free survival by duration of breastfeeding. This trial is registered withClinicalTrials.gov, numberNCT01229761 . Findings: From June 7, 2011, to April 2, 2015, 2848 HEU children were randomly assigned to receive co-trimoxazole (n=1423) or placebo (n=1425). The data and safety monitoring board stopped the study early because of a low likelihood of benefit with co-trimoxazole. Only 153 (5%) children were lost to follow-up (76 in the co-trimoxazole group and 77 in the placebo group), and 2053 (72%) received treatment continuously to age 15 months, death, or study closure. Mortality after the start of study treatment was similar in the two study groups: 30 children died in the co-trimoxazole group, compared with 34 in the placebo group (estimated mortality at 18 months 2·4% vs 2·6%; difference −0·2%, 95% CI −1·5 to 1·0, p=0·70). We saw no difference in hospital admissions between groups (12·5% in the co-trimoxazole group vs 17·4% in the placebo group, p=0·19) or grade 3–4 clinical adverse events (16·5% vs 18·4%, p=0·18). Grade 3–4 anaemia did not differ between groups (8·1% vs 8·3%, p=0·93), but grade 3–4 neutropenia was more frequent in the co-trimoxazole group than in the placebo group (8·1% vs 5·8%, p=0·03). More co-trimoxazole resistance in commensal Escherichia coli isolated from stool samples was seen in children aged 3 or 6 months in the co-trimoxazole group than in the placebo group (p=0·001 and p=0·01, respectively). 572 (20%) children were breastfed. HIV infection and mortality did not differ significantly by duration of breastfeeding (3·9% for 6 months vs 1·9% for 12 months, p=0·21). Interpretation: Prophylactic co-trimoxazole seems to offer no survival benefit among HEU children in non-malarial, low-breastfeeding areas with a low risk of mother-to-child transmission of HIV. Funding: US National Institutes of Health.